Dermatomyositis: Current Insights into Pathogenesis, Diagnosis, and Dermatologic Management - Helen Anastasya; Cut Putri Hazlianda (The Indonesian Journal of General Medicine, 2026)
INTRODUCTION: Dermatomyositis (DM) is a rare, heterogeneous, systemic autoimmune myopathy characterized by hallmark cutaneous manifestations and, typically, symmetric proximal muscle weakness. It’s clinical significance is profound, extending beyond the skin and muscle to involve systemic complications such as interstitial lung disease (ILD) and a strong association with internal malignancy, both of which confer significant morbidity and mortality. The field is currently undergoing a paradigm shift, moving from a monolithic clinical diagnosis to a "clinico-serological" classification based on myositis-specific autoantibodies (MSAs). This modern approach is essential for accurate prognosis and the selection of targeted therapies. METHODS: This article presents a comprehensive narrative literature review based on a targeted search of scientific databases, including PubMed/MEDLINE, Google Scholar, and Scopus. The search prioritized literature published between 2020 and 2024 to capture the most current insights. Key search terms included "Dermatomyositis," "pathogenesis," "diagnosis," "treatment," "myositis-specific autoantibodies," "Type I interferon," "Janus Kinase inhibitors," "malignancy screening," and "interstitial lung disease." Selected foundational articles were included for essential context, and all literature was synthesized to build an integrated framework. LITERATURE REVIEW: Recent advances have solidified the central role of the Type I interferon (IFN-I) pathway in DM pathogenesis, creating a "Type I IFN signature" in affected skin, muscle, and blood. This discovery provides a direct mechanistic rationale for emerging targeted therapies. The identification of MSAs has revolutionized the diagnostic and prognostic landscape. These autoantibodies define distinct, clinically relevant phenotypes, such as anti-MDA5-positive DM, which is associated with rapidly progressive ILD (RP-ILD) (Lu, Peng and Wang, 2024), and anti-TIF1-γ-positive DM, which carries a very high risk of concurrent malignancy. Diagnosis now integrates clinical findings, serological profiling, and imaging, with new 2024 IMACS guidelines providing a risk-stratified, MSA-driven protocol for malignancy screening. Dermatologic management follows a stepwise algorithm, beginning with foundational photoprotection and antimalarials, escalating to conventional immunosuppressants (e.g., mycophenolate mofetil, methotrexate), and advancing to intravenous immunoglobulin (IVIG) and rituximab for refractory disease. Janus kinase (JAK) inhibitors represent the most promising emerging therapy, as they directly target the pathogenic IFN-STAT signaling pathway. CONCLUSION: The modern management of DM is a multidisciplinary, personalized endeavor guided by a patient's specific clinico-serological profile. This approach enables vital risk stratification for ILD and malignancy, guiding both screening and therapeutic selection. While significant therapeutic gaps remain, particularly for anti-MDA5+ RP-ILD and refractory cutaneous disease, the development of pathway-specific therapies like JAK inhibitors heralds a new, more targeted era for DM treatment. Future research must focus on validating these new therapies in randomized controlled trials and refining classification criteria to include skin-predominant disease.